2014
DOI: 10.1002/pon.3737
|View full text |Cite
|
Sign up to set email alerts
|

Emotion episodes during psychotherapy sessions among women newly diagnosed with gynecological cancers

Abstract: Objective To describe emotion episodes during early and late psychotherapy sessions among women newly diagnosed with gynecological cancer and to examine whether the total number of emotional episodes during early and later sessions were associated with baseline psychological distress, dispositional emotion expressivity, and patient-rated therapeutic progress. Methods The study utilized data from an ongoing study examining the efficacy of two psychotherapy interventions, a coping and communication interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Younger age and higher distress were associated with higher EXP. These findings are consistent with prior work which found that more distressed women tended to express more EEs during sessions, regardless of self-reported levels of emotional expressivity (Myers Virtue et al, 2015). The therapy environment may provide a safe place in which to express distress or negative emotions that women are experiencing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Younger age and higher distress were associated with higher EXP. These findings are consistent with prior work which found that more distressed women tended to express more EEs during sessions, regardless of self-reported levels of emotional expressivity (Myers Virtue et al, 2015). The therapy environment may provide a safe place in which to express distress or negative emotions that women are experiencing.…”
Section: Discussionsupporting
confidence: 91%
“…EXP was rated from EEs, which were identified using the emotion episode coding system (Greenberg & Korman, 1993; Korman, 1998). More details regarding EE coding are provided by Myers Virtue and colleagues (2015). Using transcripts and accompanying videos, each EE within a session was rated on a 7-point scale in terms of participant awareness of, and exploration and reflection on, their inner experience to achieve self-understanding and problem resolution (Klein et al, 1969).…”
Section: Methodsmentioning
confidence: 99%
“…This study explored levels of emotional awareness during therapy sessions delivered to women who were newly diagnosed with gynecologic cancer. We expanded our prior work (Manne et al, 2017; Myers Virtue et al, 2015) by describing emotional awareness and its correspondence with emotional processing. The study had four key findings.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement was 90.6%. See prior work (Myers Virtue et al, 2015) for further details about coding. EEs were transcribed for further coding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation